2014
DOI: 10.1364/ao.53.006742
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-dependent elliptical crater morphologies formed on a silicon surface by single-shot femtosecond laser ablation

Abstract: Formation of the elliptical-shaped craters on a silicon surface is investigated comprehensively using a single shot of a femtosecond laser. It is observed that the ablation craters are elongated along the major axis of the polarization direction, while their orientation is parallel to the polarization direction. The ablation area grows and the morphology of the craters evolves from an ellipse to nearly a circle with increasing fluence. The underlying physical mechanism is revealed through numerical simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Polarization dependent single pulse ablation has been previously observed in silicon [27] and in PMMA [26] where the overall features of the ablation crater were found to be elongated along the major axis of the polarization vector. In contrast, in silicon only the rim dimensions were found to be polarization sensitive while the ablation crater remained circular.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Polarization dependent single pulse ablation has been previously observed in silicon [27] and in PMMA [26] where the overall features of the ablation crater were found to be elongated along the major axis of the polarization vector. In contrast, in silicon only the rim dimensions were found to be polarization sensitive while the ablation crater remained circular.…”
Section: Discussionmentioning
confidence: 80%
“…Numerical simulation of the interaction of intense light pulses with solids demonstrated that the polarization dependence of the ablation features arise from a local field enhancement during light-plasma interaction. Recently, single shot femtosecond laser ablation of silicon also demonstrated formation of elliptical-shaped craters that were elongated along the major axis of the polarization direction [27]. The morphology of the ablation craters was found to evolve from an ellipse to nearly a circle with increasing fluence.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon has been reported in previous studies on femtosecond laser ablation of Si and Cu. 42,43 To qualitatively depict the aforementioned ellipticity of the ablated microdots, we dened parameter ellipticity as the aspect ratio of a to b, where a and b represent the lengths of the major axis and minor axis, respectively. The dependence of the ablation area and ellipticity on the laser uence is shown in Fig.…”
mentioning
confidence: 99%